1977
DOI: 10.1149/1.2133149
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation Studies of Permalloy Films by Quartz Crystal Microbalance, AES, and XPS

Abstract: THIN FILM CORROSION KINETICS subject and M. R. Lorenz for reviewing this manuscript. They are also indebted to Dr. D. W. Rice for the use of his environmental chamber and ESCA apparatus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
11
0

Year Published

1978
1978
1997
1997

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 15 publications
1
11
0
Order By: Relevance
“…4 the sNi/sFe for pure metals and alloys for Ar' energy about 1 keV was somewhat greater than unity, but no more than 1.1. The closest value was reported in Ref 5…”
supporting
confidence: 57%
“…4 the sNi/sFe for pure metals and alloys for Ar' energy about 1 keV was somewhat greater than unity, but no more than 1.1. The closest value was reported in Ref 5…”
supporting
confidence: 57%
“…Relatively few investigations dealt with the passivity of Ni-Fe alloys (6a, [18][19][20][21][22]. The air oxidation of Permalloy (Ni08Fe0.2) was studied before (20,21).…”
mentioning
confidence: 99%
“…A limited number of QCM studies under atmospheric pressure conditions have been reported, e.g., in connection with the adsorption of moisture films (2)(3)(4)(5), atmospheric corrosion in the presence of humid air containing gaseous corrosive components (6)(7), oxidation at elevated temperatures (8), and adsorption of corrosion inhibiting organic molecules on various metal surfaces (9)(10)(11).…”
mentioning
confidence: 99%